MYOSTIMULANT EFFECT OF LEAVES OF CASSIA OCCIDENTALIS (CAESALPINIACEAE) ON ISOLATED RABBIT DUODENUM - Arsene, Mea; Kouakou; Abo; Nguessa; Bi, Irie; Bi, Kahou (International Journal of Research -GRANTHAALAYAH, 2017)
The fresh leaves of Cassia occidentalis are used in the African pharmacopoeia to treat constipation and malaria. This practice is not recommended for pregnant women. In traditional medicine the fresh leaves used in enema would have abortive properties. In this work, the aqueous extract of dry leaves of Cassia occidentalis (AECo) is added to the Mc Ewan type physiological solution containing the isolated intestine muscle which is suspended between two shaped stainless steel hooks. Doses of AECo less than 10-2 mg / ml have no significant effect on duodenal contractions. For doses between 10-1 mg / ml and 4 mg / ml, baseline amplitude and tone increased from 10.12 ± 4.02% (P <0.005) to 55.37 ± 3.23% (P <0.001). Indeed, at doses of 1, 2 and 4 mg / ml, AECo leads to significant increases in the amplitude of the contractions which pass successively from 0.32 ± 0.09 mN, 0.41 ± 0.07 mN to 0.49 ± 0, 13 mN (P <0.001). Let a variation in the amplitude of the rhythmic contractions of the duodenum of 30.82 ± 3.07%, 44.32 ± 2.47% and 55.37 ± 4.23%, respectively. An increase in the amplitude and tone of rhythmic contractions is in a dose-dependent manner. The myostimulant effect is characterized by the increase of the rhythm and the amplitude of isolated intestine muscle. The effect of AECo is partially suppressed by atropine. This suggests the presence of muscarinic cholinergic compounds in this aqueous extract.